A highly flexible and self-healable rechargeable fibrous Zn–MnO2 battery. Issue 11 (7th May 2021) - Zhao, Bingtian; Wang, Min; Wang, Siliang; Ni, Tong; Wang, Qiang; Ruan, Limin; Huang, Linsheng; Zeng, Wei
Abstract : The fibrous Zn–MnO2 battery exhibits excellent flexibility and self-healability. Abstract : The current studies on fibrous batteries for portable and wearable electronic products still fall greatly behind some requirements, such as high safety, low cost, high energy density and low attenuation of electrochemical performance under a harsh environment (bent or cut). To overcome the above problems, a rechargeable fibrous Zn–MnO2 battery based on a cross-linked polyacrylamide electrolyte and modified polyurethane (PU) protective shell is realized. As expected, the device exhibits excellent electrochemical performance, i.e., a high specific capacity of 104.9 mA h cm −3 (at a current density of 0.16 A cm −3 ) and a high energy density of 234.9 mW h cm −3 with a maximum power density of 1.85 W cm −3 . In addition, the neutral aqueous electrolyte and zinc based anode contribute to the high safety and low cost of the device. More importantly, the reversible hydrogen bonding in the PU shell helps to achieve high reliability and stability of the device under a harsh environment, which is illustrated by its remarkable flexibility (a capacity retention of 81.7% at a bending angle of 150°) and self-healability (a capacity retention of 83.1% after the 5th healing). This study provides an effective strategy for exploiting high-efficiency fibrous energy storage devices with high safety, low cost, and high reliability and stability.